2016
DOI: 10.5792/ksrr.2016.28.1.62
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between Magnetic Resonance Imaging Characteristics of the Patellar Tendon and Clinical Scores in Osgood-Schlatter Disease

Abstract: PurposeThis study aims to evaluate magnetic resonance imaging (MRI) findings in young adults with symptomatic Osgood-Schlatter disease (OSD) and compare those in young adults without OSD.Materials and MethodsWe compared MRI findings between young adults with OSD (OS group, n=30) and the equivalent number of young adults without OSD (control group). Visual analog scale scores and Kujala scores were evaluated and correlation analysis was performed in the OS group.ResultsIn the OS group, MRI revealed that the pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
21
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 22 publications
(40 reference statements)
2
21
1
Order By: Relevance
“…Of the studies that reported sex and age range, 70% were male, and 30% were female, with adolescents aged from 9 to 17 years. Five studies included adults with unresolved OSD aged 18‐39 years 11‐15 . Full study characteristics are summarized in Supplemental Material, Table S1.…”
Section: Resultsmentioning
confidence: 99%
“…Of the studies that reported sex and age range, 70% were male, and 30% were female, with adolescents aged from 9 to 17 years. Five studies included adults with unresolved OSD aged 18‐39 years 11‐15 . Full study characteristics are summarized in Supplemental Material, Table S1.…”
Section: Resultsmentioning
confidence: 99%
“… 5 It is considered an apophyseal injury of the tibial tuberosity, the site of attachment of the patellar tendon onto the tibia. 1 , 11 , 15 The weak apophyseal cartilage is thought to be susceptible to injury before the apophysis is fully matured. 18 , 31 Although the etiology is not fully understood, characteristics such as cartilage swelling and associated tendon changes (including thickening of the patellar tendon and increased Doppler activity) have been documented in patients with OSD.…”
mentioning
confidence: 99%
“…On the contrary, there are documented cases of adults with residual symptoms/sequalae resulting from OSD. 3 , 15 , 21 , 28 A retrospective study from Krause and colleagues 13 in 1990 stated that at long-term follow-up (mean, 9 years), as many as 1 in 4 patients had continuing additional symptoms into adulthood. The extent of the severity and impact on sport, physical activity, and life in this group was not documented.…”
mentioning
confidence: 99%
“…[1][2][3] The etiology of the disease has not yet been fully clarified; however, several authors tried to explain the underlying pathologies, as they have identified some potential risk factors and proposed various theories about the etiology. [3][4][5][6][7][8][9][10] Although some authors have shown an association between OSD and shortness of the rectus femoris muscle, others have claimed that limited foot dorsiflexion played a role in the etiology of the disease. 7,9 Guler et al drew attention to the positive relationship between OSD and attention deficit hyperactivity disorder (ADHD).…”
mentioning
confidence: 99%
“…1 Although it has been defined as an overuse syndrome seen in highly active children but it is not seen in every child who does the same sporting activity and performance. 4,5 Thus, there may be some subtle anatomic characteristics or variations of the knee extensor mechanism, such as patellofemoral alignment that is responsible for the emergence of OSD. 6,7 In other words, some children may be predisposed to developing OSD due to certain anatomic variations in the extensor mechanism.…”
mentioning
confidence: 99%